Analysis of Spun Pile Bearing Capacity Based on Spt Data Using Analytical and Software Modeling Approaches - Dicky Hamdani Tampubolon; Tika Ermita Wulandari (LPPM Universitas Andalas, 2026)
Foundations are crucial structural elements that support the entire building load. At the study site, soil conditions are variable and complex, consisting of clay and sand layers with non-uniform bearing capacity, making accurate foundation capacity assessment essential. This study compares the bearing capacity of spun piles using analytical calculation with the Luciano Decourt method, numerical modeling with GEO5 software, and field verification through PDA Tests. SPT values were used as input for both calculation methods. Results indicate that the analytical method predicts a bearing capacity of 202.41 tons, lower than the PDA Test result of 296.7 tons, while GEO5 modeling produces 361.48 tons, closer to field conditions. The difference arises because the analytical method relies on a simplified SPT-based calculation, whereas GEO5 processes soil data into more detailed parameters and computes soil response at each layer incrementally. These findings confirm that numerical modeling provides a more representative estimate of bearing capacity, while differences with analytical calculations remain acceptable in geotechnical practice. This study offers a reliable reference for designing spun pile foundations on complex soils, enhancing design accuracy and structural safety.